Brief report: Moving prevention into schools: The impact of a trauma‐informed school‐based intervention. (25th June 2015) - Mendelson, Tamar; Tandon, S. Darius; O'Brennan, Lindsey; Leaf, Philip J.; Ialongo, Nicholas S.
ABSTRACT: Adolescents in disadvantaged communities have high rates of exposure to stress and trauma, which can negatively impact emotion regulation and executive functioning, increasing likelihood of school problems. This pilot study evaluated RAP Club, a 12‐session school‐based trauma‐informed group intervention co‐facilitated by a mental health counselor and young adult community member that utilizes evidence‐based cognitive‐behavioral and mindfulness strategies. Seventh and eighth graders at two urban public schools serving low‐income communities were assigned to receive RAP Club ( n  = 29) or regular school programming ( n  = 20). RAP Club improved teacher‐rated emotion regulation, social and academic competence, classroom behavior, and discipline. Higher program dose predicted improvements in several teacher‐rated outcomes. Student self‐report outcomes, however, did not vary by study group or dose. Even students with low baseline depression showed improvement in teacher‐rated outcomes following program participation, supporting a model of universal program delivery to all students. Findings suggest RAP Club merits further study.